Faktor Risiko Keluhan Musculoskeletal pada Tukang Fotokopi di Kota Cimahi - Gurdani Yogisutanti; Dameria Noviana Habeahan; Suhat (Media Kesehatan Masyarakat Indonesia, 2020)
The activity of photocopying can not be avoided from office activities and education. Photocopier risk having musculoskeletal complaints. This study aimed of determine the risk factors for musculoskeletal disorders in photocopier. Respondents were taken by accidental sampling obtained as many as 84 operators. The research design used was observational research with cross sectional approach. The instrument to measure work attitudes was REBA (Rapid Entire Body Assessment) and MSDs using NBM (Nordic Body Map). Data collection was carried out by means of interviews, observations, taking pictures and measuring the work position of the photographer. The statistical test used was chi square at a 5% significance level. The results of statistical analysis concluded that there was no relationship between age (p=0.260), gender (p=0.290), level of education (p=1.000), marital status (p=0.727), status ownership of photocopy (p=1.000), number of copies (p=0.122), smoking habits (p=1.000) and length of service (p=1.000) with musculoskeletal complaints, but there is a relationship between length of work (p=0.026) and work attitude (p=0.001) with musculoskeletal complaints. The recommended advice is the need for counseling on ergono-mics and occupational safety and health for owners and photocopier.